Computed Tomography Scan Orbita on suspicion of tumors in the General Hospital Haji Adam Malik: Computed Tomography Scan Orbita on suspicion of tumors in the General Hospital Haji Adam Malik - Liberti Tarin; Juliana Lasniar Sidauruk; Bernat Redearman Lumban Gaol (Journal of Midwifery and Nursing, 2020)
Is a collection of abnormal cell tumors formed by cells that grow continuously - and again, it is not limited, it is not coordinated with the surrounding tissue and are not useful to the body. Tumor tebagi two: namely malignant tumors (malignant) and benign tumors (benign). The eye is the optical system that focuses the light beam on the photoreceptor, which converts light energy into nerve impulses. With a tumor of the orbit will change the shape of anatomy and function of the eye that can cause vision disturbances for the sufferer. CT scan is a radiological technique to show the anatomy of the orbit and kelainannnya. The author uses the tool brands Asteion CT Scan, 4 slice. The test results showed a tumor of the orbit.